Pengaruh Populasi Nematoda Puru Akar (Meloidogyne graminicola) terhadap Pertumbuhan dan Hasil Padi - Mulyadi Mulyadi (Jurnal Perlindungan Tanaman Indonesia, 1997)
The objective of the research wwas to evaluate the effect of initial population levels of Meloidogyne graminicola on growth and yield of rice especially cultivated IR64. Initial population levels of Meloidogyne graminicola used were: 0; 0.25; 0.5; 1.0; 2.0; 4.0; 8.0; and 16.0 larvae/ml of soil. The research results were: 1) M. graminicola did not influence rice seedling emergence; 2) seedling death was found at 20 days after sowing, 70% of seedling died 30 days after sowing at the population level of 16.0 larvae/ml of soil; 3) the yield of rice decreased up to 38.45% in pot inoculated with M. graminicola at 16.0 larvae/ml of soil; 4) the relationship between yield and initial population of M. graminicola is described by the equation Y=m+(1-m)z^P.T where m = 0.66, z= 0.96, and T= 1.0.